Opinions of Future Pedagogues on Educational System Changes Highlighted by the Mass Media - Przybylski, Błażej (Przegląd Badań Edukacyjnych (Educational Studies Review), 2017)
The article is a report of the author’s research conducted among students of the Maria Grzegorzewska University in Warsaw in the years 2015 and 2016. The aim of the research was to recognise the students’ political views, attitudes towards democracy and electoral activity, as well as their opinion on issues popular in the mass media, such as liquidation of gymnasium and switching to the 8-grade primary school and the abolition of the obligatory school enrolment age of 6 years. The research was conducted by the author’s questionnaire containing 16 closed-ended questions. The participants were 506 stationary students of the Pedagogical Faculty at the Maria Grzegorzewska University, specialization: pedagogy and special education. The group of participants was selected randomly. The results of the research prove unambiguously that the interest in politics is very low among students; the majority of them do not have any precise views and half of them declared not having participated in the elections for Parliament. Concerning the students’ attitude towards the proposed changes in the educational system, the percentage rate shows that both proposals of the Polish government (liquidation of gymnasium and abolition of the obligatory school enrolment age of 6 years) have more supporters than opponents. The author confronts the obtained results with the results of research undertaken by large research centres on all-Poland research groups, which allows to present the attitudes of pedagogy students on the background of the general public.